Young children show more vigilance against individuals with poor knowledge than those with antisocial motives. Issue 3 (17th January 2018) - Vanderbilt, Kimberly E.; Heyman, Gail D.; Liu, David
Abstract: In three experiments, the present research investigated whether children's distrust of unreliable informants was influenced by the type of mental state causing the informants' unreliability. Children (total N = 167) played a searching game with an informant who repeatedly provided incorrect information either due to poor knowledge or to intentional deception resulting from antisocial motives. Results of Experiment 1 showed that children initially distrusted the ignorant informant more than the deceptive informant, but that levels of distrust increased and converged after children received feedback on their responses. Experiment 2 replicated the findings of Experiment 1 and also extended them by showing that children consistently distrusted the ignorant informant more than the deceptive informant in the absence of feedback. Experiment 3 helped rule out the possibility that results could be explained by the wording of informant descriptions in Experiments 1 and 2. Taken together, our results contribute to a small body of findings suggesting that young children have the capacity to use mental state information to make selective trust judgments and suggest that young children show more vigilance against individuals with poor knowledge than those with antisocial motives. Highlights: How does the type of mental state causing unreliability (either ignorance or antisocial motives) influence children's vigilance against unreliable sources? A direct comparison showed that children (3 ‐ 4 years old) distrusted ignorant sources more than antisocial sources. Children use mental state information to make selective trust judgements.